2016
DOI: 10.7754/clin.lab.2015.150927
|View full text |Cite
|
Sign up to set email alerts
|

A Controversial New Approach to Address Hematological Parameters in Hashimoto's Thyroiditis

Abstract: A single marker or panel of biomarkers is not a consistent indicator of HT, but NLR combined with PLR testing may offer a more reliable diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However above mentioned study from Arpaci D et al studied MPV parameter in Hashimoto Thyroiditis but had found no significance. 25 Limitations of the study: This is a single-center study is a relatively small number of cases and a limited follow-up period. For example, sometimes the development of permanent hypothyroidism may extend to 12 months, but unfortunately, we were unable to get 12 months of data for most of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However above mentioned study from Arpaci D et al studied MPV parameter in Hashimoto Thyroiditis but had found no significance. 25 Limitations of the study: This is a single-center study is a relatively small number of cases and a limited follow-up period. For example, sometimes the development of permanent hypothyroidism may extend to 12 months, but unfortunately, we were unable to get 12 months of data for most of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MPV parameter was also examined but no significant differences were found as in our study. 25 Neutrophil to Lymphocyte Ratio and PLR in Thyroid Cancer have been investigated in many studies as well. [26][27][28][29] Significant correlations between NLR and PLR and prognostic factors were recorded in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors proved that NLR may be a useful parameter in the differential diagnosis of benign thyroid nodules from malignant tumors, especially papillary thyroid carcinoma [ 17 , 37 , 38 ]. Aside from thyroid neoplasms, NLR combined with PLR have been studied as potential indicators of Hashimoto’s disease occurrence, which can allow to distinguish patients with chronic autoimmune thyroiditis from healthy individuals [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NLR and PLR could serve as indicators to differentiate malignant from benign thyroid nodules in preoperative period as well as they may be predictors of response to treatment, progression of the disease, risk of recurrence, and mortality rate in thyroid cancers [ 17 , 18 , 19 , 20 ]. Literature data about the role of NLR, MLR and PLR in chronic autoimmune thyroid diseases are still lacking [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. There are only single studies evaluating the relationship between these direct and indirect blood-cell associated inflammatory markers and GO [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association of elevated NLR with advanced disease and prognosis has been elucidated quite well in various malignancies (15,16). In addition, NLR has been elevated in autoimmune diseases like systemic lupus erythematosus (SLE) (9,25,26), rheumatoid arthritis (RA) (10), Sjögren's syndrome (27), and autoimmune thyroiditis (28,29). Also, increased NLR was shown to be an indicator of disease activity in SLE (26), RA (10,30), and Sjögren syndrome (27).…”
Section: Discussionmentioning
confidence: 99%